The Determinants of Corporate Social Responsibility Disclosure: Empirical Evidence from Indonesia Listed Firms - Sofik Handoyo (Journal of Accounting Auditing and Business, 2020)
The study was motivated by previous research findings that indicate the variations of corporate social responsibilities disclosure among countries. The purpose of the study is to examine the determinants that influence corporate social responsibilities disclosure. The determinants namely the firm size, firm age, earning per share, stock price, and industry type, were examined. The sample of the study is listed firms in Indonesia Stock Exchange that issued sustainability reporting. Content analysis of sustainability reporting using the global reporting initiative standard was conducted to measure corporate social responsibilities disclosure. The determinants were examined using multiple regression analysis with a confidence interval level of 95%. The results indicated that the firm size, earning per share and stock price significantly influence the corporate social responsibilities disclosure. Empirical findings of the study contribute in terms of giving an understanding of practice corporate social responsibilities disclosure in a developing country, especially in the Southeast Asia region. Furthermore, the findings provide valuable information for conducting cross-countries' comparative studies.